Improvement of a rivet geometry for the self-piercing riveting of high-strength steel and multi-material joints - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Production Engineering)
As a result of lightweight design, increased use is being made of high-strength steel and aluminium in car bodies. Self-piercing riveting is an established technique for joining these materials. The dissimilar properties of the two materials have led to a number of different rivet geometries in the past. Each rivet geometry fulfils the requirements of the materials within a limited range. In the present investigation, an improved rivet geometry is developed, which permits the reliable joining of two material combinations that could only be joined by two different rivet geometries up until now. Material combination 1 consists of high-strength steel on both sides, while material combination 2 comprises aluminium on the punch side and high-strength steel on the die side. The material flow and the stress and strain conditions prevailing during the joining process are analysed by means of numerical simulation. The rivet geometry is then improved step-by-step on the basis of this analysis. Finally, the improved rivet geometry is manufactured and the findings of the investigation are verified in experimental joining tests.
Keywords: Self-piercing riveting; Joining technology; Rivet geometry; Multi-material design; High-strength steel; Aluminium

A micromechanical-based finite element simulation of process-induced residual stresses in metal-CFRP-hybrid structures - Tinkloh, Steffen Rainer; Wu, Tao; Tröster, Thomas; Niendorf, Thomas (Composite Structures)

Probability Distribution of Joint Point Loadings in Car Body Structures under Global Bending and Torsion - Martin, Sven; Camberg, Alan A.; Tröster, Thomas (Procedia Manufacturing)

CFD Simulation of Film and Rivulet Flows on Microstructured Surfaces - Bertling, René; Hack, Mathias; Ausner, Ilja; Kenig, Eugeny

Microstructural investigation on phase transformation during flow forming of the metastable austenite AISI 304 - Rozo Vasquez, Julian; Arian, Bahman; Riepold, Markus; Homberg, Werner; Trächtler, Ansgar; Walther, Frank (54. Metallographie-Tagung)

Realization of all-optical vortex switching in exciton-polariton condensates - Ma, Xuekai; Berger, B; Aßmann, M; Driben, R; Meier, Torsten; Schneider, C; Höfling, S; Schumacher, Stefan (Nature Communications)

Federico Fellini’s Sanctifying Effect. - Ahrens, Stephan (Journal of Italian Cinema & Media Studies 9, Nr. 1)

Vom Klang bewegt. Das Kino und Ludwig van Beethoven. - Ahrens, Stephan

Offensive Sensation. Ein Porträt von Melina Mercouri - Ahrens, Stephan (Dschungel (jungle World))

Glücklich ohne Happy End - Ahrens, Stephan (in die tageszeitung)

Das Stadtgespräch - Ahrens, Stephan (Dschungel (Jungle World))

In memoriam Sarah Maldoror - Ahrens, Stephan

Eine andere Welt, Porträt Stéphane Brizé - Ahrens, Stephan

IRiS – Intelligente Rettung im SmartHome - Schultz, Andreas Maximilian; Lamers, Christoph; Koch, Rainer; Lüke, Richard; Sauerland, Torben (vfdb-Zeitschrift)

Ferres vor/neben/mit/am … – Instagrammatikalische Präpositionen - Eckel, Julia (Exzess und Entzug: Ferres vor Gursky, Ferres vor Immendorff)

Re/Dis-Solved Selves: (Re)Searching Selfies, (Inter)Facing the Face - Eckel, Julia (Re-/Dissolving Mimesis)

The Work of Entanglement. Translating Women's Rights in Malaysia - Spiegel, Anna (Multiple Gender Cultures, Sociology and Plural Modernities. Re-reading Social Constructions of Gender across the Globe in a De-Colonial Perspective.)

Wissen in der Transnationalisierung. Zur Ubiquität und Krise der Übersetzung

Long- and Short-Term Tensile Strength and Morphology of Joined Beta-Nucleated Polypropylene Parts - Wübbeke, Andrea; Schöppner, Volker; Paul, André; Tiemann, Michael; Austermeier, Laura; Fitze, Marcus; Chen, Mingie; Jakob, Fabian; Heim, Hans-Peter; Wu, Tao; Niendorf, Thomas; Röhricht, Marie-Luise; et al. (SPE ANTEC 2020: The Virtual Edition 5)
This paper presents the results of static short-term and long-term tensile tests for beta-nucleated joined polypropylene samples by the hot plate welding process. In the present study different dimensionless joining displacements are accounted for. The results show that high short-term tensile strength does not directly transfer to high long-term tensile strength. The morphology of the weld seam in the joined samples is examined by means of transmitted and reflected light microscopy. For the dimensionless joining displacements of 0.75 and 0.95, stretched spherulites are obtained. X-Ray diffraction can be used as a tool for qualitative and quantitative analysis and eventually for differentiation of samples of various joining displacements.

Investigation of residual stresses of hot plate welding - Schöppner, Volker; Wübbeke, Andrea; Geißler, B.; Schmidt, M.; Maginer, A.; Wu, T.; Niendorf, T.; Jakob, F.; Heim, H. (73rd Annual Assembly of the International Institute of Welding (IIW))

Selected Aspects for the Assessment of Laser Transmission Welding - Schöppner, Volker; Wübbeke, Andrea; Schriegel, Fabian; Paul, Andrej; Tiemann, Michael; Geißler, Bastian; Schmidt, Michael; Magnier, Arnaud; Niendorf, Thomas (Joining Plastics)
In diesem Artikel werden das Scherzugverhalten und der morphologische Zustand von konturgeschweißtem Polypropylen (PP) mit einem Massenanteil von 0,2% Ruß untersucht. Dabei zeigen die Ergebnisse ...

LONG- AND SHORT-TERM TENSILE STRENGTH AND MORPHOLOGY OF JOINED BETA-NUCLEATED POLYPROPYLENE PARTS - Schöppner, Volker; Wübbeke, Andrea; Paul, A.; Tiemann, M.; Austermeier, Laura; Fitze, M.; Chen, M.; Jakob, F.; Heim, H.-P-; Wu, T.; Niendorf, T.; Röhricht, M.-L.; et al. (ANTEC20)

Joining with Versatile Friction-Spun Joint Connectors - Rostek, Tim; Wiens, Eugen; Homberg, Werner (Procedia Manufacturing)

Some ideas for the further development of hydroforming process chains - Wiens, Eugen; Djakow, Eugen; Homberg, Werner (Nebu/Nehy 2020)
Even though the spectrum of parts is expected to shift over the long term as a result of increasing e-mobility, there is still an extremely high demand for complex components made of high-strength materials which can only be produced by hydroforming technologies. The innovative combination of hydroforming processes with other forming processes, as well as the improvement of the processes themselves, offers considerable potential for improvement. A number of promising ways of improving the hydroforming process chain are therefore the subject of this contribution. The focus of the article is on possible approaches for combining (incremental) pre- and post-forming operations, which can permit considerable improvements in both quality and features at a reduced cost. Furthermore, a novel combination of quasi-static and high-speed forming processes is presented, leading to an improved overall forming process (with a high application potential) for the production of complex parts.
Keywords: Hydroforming; Incremental Forming; Internal Flow-turning; High-speed Forming

Cohen-Macaulay modules over the algebra of planar quasi-invariants and Calogero-Moser systems - Burban, Igor; Zheglov, A. (Proceedings of the London Mathematical Society)
In this paper, we study properties of the algebras of planar quasi-invariants. These algebras are Cohen–Macaulay and Gorenstein in codimension one. Using the technique of matrix problems, we classify all Cohen–Macaulay modules of rank one over them and determine their Picard groups. In terms of this classification, we describe the spectral modules of the planar rational Calogero–Moser systems. Finally, we elaborate the theory of the algebraic inverse scattering method, providing explicit computations of some ‘isospectral deformations’ of the planar rational Calogero–Moser system in the case of the split rational potential.

Digitalisierung in der Lehrerbildung durch Communities of Practice. Konzeption, Governance und Qualitätsmanagement des ComeIn-Verbundvorhabens in Nordrhein-Westfalen - van Ackeren, Isabell; Buhl, Heike M.; Eickelmann, Birgit; Heinrich, Martin; Wolfswinkler, Günther (Bildung, Schule und Digitalisierung)

Digitalisierungsbezogene Berufswahlneigung und Sichtweisen von Mädchen und Jungen auf die Relevanz digitaler Medien für die Gesellschaft - Labusch, Amelie; Eickelmann, Birgit; Drossel, Kerstin; Vennemann, Mario (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Schulschließungen und Perspektiven für die Pandemie-Zeit –– Ergebnisse der Studie ‚Schule auf Distanz‘ - Eickelmann, Birgit; Drossel, Kerstin (SchulVerwaltung BW)

Fortbildung im digitalen Zeitalter. Editorial - Eickelmann, Birgit; Kummer Wyss, Annemarie (Journal für Schulentwicklung)

ICILS 2018 #Transfer. Gestaltung digitaler Schulentwicklung in Deutschland - Labusch, Amelie; Eickelmann, Birgit; Conze, Daniela

Wünsche zur schulischen Nutzung digitaler Medien, digitalisierungsbezogene Berufswahlneigung und Sichtweisen von Schülerinnen und Schülern auf die Relevanz digitaler Medien für die Gesellschaft - Eickelmann, Birgit; Drossel, Kerstin; Labusch, Amelie; Heldt, Melanie (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Selbsteingeschätzte Kompetenzen von Lehrkräften zum schulischen Einsatz digitaler Medien - Drossel, Kerstin; Lorenz, Ramona; Labusch, Amelie; Eickelmann, Birgit (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Kompetenzen im Bereich ‚Computational Thinking‘ von Mädchen und Jungen - Labusch, Amelie; Eickelmann, Birgit; Gerick, Julia; Drossel, Kerstin (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Lehrkräftekooperation im Kontext des Lernens und Lehrens mit digitalen Medien - Drossel, Kerstin; Eickelmann, Birgit (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Schulischer IT-Support: Sichtweisen und Zuständigkeiten - Eickelmann, Birgit; Drossel, Kerstin; Labusch, Amelie (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Schulische IT-Ausstattung und Wahrnehmung der IT-Ausstattungsqualität - Labusch, Amelie; Eickelmann, Birgit; Drossel, Kerstin (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Lehrer*innenbildung in virtuellen Lernnetzwerken – Warum engagieren sich Lehrkräfte im #twitterlehrerzimmer? - Conze, Daniela; Drossel, Kerstin; Eickelmann, Birgit (Bildung, Schule und Digitalisierung)

Anlage der Studie ICILS 2018-NRW - Eickelmann, Birgit; Labusch, Amelie; Drossel, Kerstin; Vennemann, Mario (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Schulschließungen und Perspektiven für die Pandemie-Zeit - Ergebnisse der Studie ‚Schule auf Distanz‘ - Eickelmann, Birgit; Drossel, Kerstin (SchulVerwaltung NRW)

ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich

Miradas francesas sobre Gernika y Guernica - Schreckenberg, Stefan (Guernica entre ícono y mito. Productividad y presencia de memorias colectivas)

Anchoring Points as a Method for Interdisciplinary Systems Engineering with the New V-Model - Gräßler, Iris; Hentze, Julian; Hesse, Philipp (Proceedings of TMCE Conference 2020)

Entwicklung von Selbstlern- und Medienkompetenz im Homeschooling – Chancen und konzeptionelle Anforderungen - Gerhardts, L.; Kamin, A.M.; Meister, Dorothee M.; Richter, L.; Teichert, Jeannine (PraxisForschungLehrer*innenBildung)

Lernen auf Distanz – Einblicke in den familialen Alltag des Homeschoolings und Formen der Bewältigung - Gerhardts, L.; Kamin, A.M.; Meister, Dorothee M.; Richter, L.; Teichert, Jeannine (Medienimpulse)

Ich habe auch Facebook-Freunde“ – Erinnerungspraktiken in vergangenen Freundschaften - Teichert, Jeannine (merzWissenschaft)

Flows on signed graphs without long barbells - Lu, You; Luo, Rong; Schubert, Michael; Steffen, Eckhard; Zhang, Cun-Quan (SIAM J. Discrete Math)

Unions of 1-factors in r-graphs and overfull graphs - Jin, Ligang; Steffen, Eckhard (J. of Combinatorics)

Exploring Non-Equilibrium Molecular Dynamics of Mobile Protons in the Solid Acid CsH2PO4 on the Micrometer and Microsecond Scale - Dreßler, C.; Kabbe, G.; Brehm, Martin; Sebastiani, D. (J. Chem. Phys.)

Dissolving Cellulose in 1,2,3-Triazolium- and Imidazolium-Based Ionic Liquids with Aromatic Anions - Brehm, Martin; Radicke, J.; Pulst, M.; Shaabani, F.; Sebastiani, D.; Kressler, J. (Molecules)

Characterization of Aqueous Lower Polarity Solvation Shells Around Amphiphilic TEMPO Radicals in Water - Hunold, J.; Eisermann, J.; Brehm, Martin; Hinderberger, D. (J. Phys. Chem. B)

From Flat to Tilted: Gradual Interfaces in Organic Thin Film Growth - Scarbath-Evers, L.; Hammer, R.; Golze, D.; Brehm, Martin; Sebastiani, D.; Widdra, W. (Nanoscale)

Dynamical Matrix Propagator Scheme for Large-Scale Proton Dynamics Simulations - Dreßler, C.; Kabbe, G.; Brehm, Martin; Sebastiani, D. (J. Chem. Phys.)

Exploring Free Energy Profiles of Enantioselective Organocatalytic Aldol Reactions under Full Solvent Influence - Weiß, M.; Brehm, Martin (Molecules)

TRAVIS – A Free Analyzer for Trajectories from Molecular Simulation - Brehm, Martin; Thomas, M.; Gehrke, S.; Kirchner, B. (J. Chem. Phys.)

Simple Determination of Fast Curing Parameters for Bonded Structures - Ditter, Jan; Aubel, Tobias; Meschut, Gerson (adhesion ADHESIVES + SEALANTS)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Joining and Disjoining Concepts for Adhesive Bonded Lightweight Structures - Ditter, Jan; Meschut, Gerson; Wibbeke, Tim Michael (adhesion ADHESIVES + SEALANTS)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Restricting ankle dorsiflexion does not mitigate the benefits of external focus of attention on landing biomechanics in healthy females - Haines, Mackenzie; Murray, Amanda M.; Glaviano, Neal R.; Gokeler, Alli; Norte, Grant E. (Human Movement Science)
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

Healthy subjects with lax knees use less knee flexion rather than muscle control to limit anterior tibia translation during landing - Keizer, Michèle N. J.; Hijmans, Juha M.; Gokeler, Alli; Benjaminse, Anne; Otten, Egbert (Journal of Experimental Orthopaedics)
Abstract Purpose It has been reported that there is no correlation between anterior tibia translation (ATT) in passive and dynamic situations. Passive ATT (ATTp) may be different to dynamic ATT (ATTd) due to muscle activation patterns. This study aimed to investigate whether muscle activation during jumping can control ATT in healthy participants. Methods ATTp of twenty-one healthy participants was measured using a KT-1000 arthrometer. All participants performed single leg hops for distance during which ATTd, knee flexion angles and knee flexion moments were measured using a 3D motion capture system. During both tests, sEMG signals were recorded. Results A negative correlation was found between ATTp and the maximal ATTd (r = − 0.47, p = 0.028). An N-Way ANOVA showed that larger semitendinosus activity was seen when ATTd was larger, while less biceps femoris activity and rectus femoris activity were seen. Moreover, larger knee extension moment, knee flexion angle and ground reaction force in the anterior-posterior direction were seen when ATTd was larger. Conclusion Participants with more ATTp showed smaller ATTd during jump landing. Muscle activation did not contribute to reduce ATTd during impact of a jump-landing at the observed knee angles. However, subjects with large ATTp landed with less knee flexion and consequently showed less ATTd. The results of this study give information on how healthy people control knee laxity during jump-landing. Level of evidence III
Keywords: Orthopedics and Sports Medicine

Sagittal knee kinematics in relation with the posterior tibia slope during jump landing after an anterior cruciate ligament reconstruction - Keizer, Michèle N. J.; Hijmans, Juha M.; Gokeler, Alli; Otten, Egbert; Brouwer, Reinoud W. (Journal of Experimental Orthopaedics)
Abstract Purpose An increased posterior tibia plateau angle is associated with increased risk for anterior cruciate ligament injury and re-rupture after reconstruction. The aims of this study were to determine whether the tibia plateau angle correlates with dynamic anterior tibia translation (ATT) after an anterior cruciate ligament reconstruction and whether the tibia plateau angle correlates with aspects of knee kinematics and kinetics during jump landing. Methods Thirty-seven patients after anterior cruciate ligament reconstruction with autograft hamstring tendon were included. Knee flexion angle and knee extension moment during single leg hops for distance were determined using a motion capture system and the dynamic ATT with its embedded method. The medial and lateral posterior tibia plateau angle were measured using MRI. Moreover, passive ATT was measured using the KT-1000 arthrometer. Results A weak negative correlation was found between the maximal dynamic ATT and the medial tibia plateau angle ( p = 0.028, r = − 0.36) and between the maximal knee flexion angle and the lateral tibia plateau angle ( p = 0.025, r = − 0.37) during landing. Patients with a smaller lateral tibia plateau angle show larger maximal knee flexion angle during landing than the patients with larger lateral tibia plateau angle. Also, the lateral tibia plateau angle is associated the amount of with muscle activity. Conclusion The posterior medical tibia plateau angle is associated with dynamic ATT. The maximal knee flexion angle and muscle activity are associated with the posterior lateral tibia plateau angle. Level of evidence III
Keywords: Orthopedics and Sports Medicine

Training athletes with an external attentional focus enhances athletic performance during countermovement jump - Letafatkar, Amir; Rabiei, Pouya; Ghanati, Hadi Abbaszadeh; Khosrokiani, Zohre; Ghahremani, Naji; Gokeler, Alli (Sport Sciences for Health)
Keywords: Orthopedics and Sports Medicine

Weitsichtigkeit zur Bildung stabiler Koalitionen - eine spieltheoretische Analyse - N., N.

Verhandeltes strategisches Verhalten - N., N.

Kronzeugenprogramme zur Aufdeckung von Kartellen - Eine spieltheoretische Analyse - N., N.

Eine ökonomische Analyse der Piraterie in zweiseitigen Softwaremärkten - N., N.

Kulturelle Unterschiede beim Lösen von Verhandlungsproblemen - N., N.

Productivity optimization through project matching - N., N.

Matching Mechanisms and Organ Exchange - N., N.

Cartel Fines in the European Union - N., N.

Anspruchsregeln in Verhandlungen - N., N.

Die Zusammenstellung eines Sortiments als Beispiel interdependenter Verhandlungen - N., N.

Matching in Netzwerken - N., N.

A Framework for Measurable Value Propositions of Mobile Applications - N., N.

Model-Based Product Configuration in Augmented Reality Applications - N., N.

Design and Implementation of a Crowd-based Prototype Validation Platform - N., N.

Alltagssituation in der Kita: Ramadan feiern in der Kita - Kamcili-Yildiz, Naciye (Religionspädagogik für Erzieherinnen. Ein ökumenisches Arbeitsbuch)

Interreligiöse Kooperation im Religionsunterricht: Perspektiven und Zwischenfazit zum Lernen in heterogenen Lerngruppen - Kamcili-Yildiz, Naciye; Woppowa, Jan; Caruso, Carina; Konsek, Lukas (Religion in der Schule. Pädagogische Praxis zwischen Diskriminierung und Anerkennung)

,Dann mache ich einfach mal weiter.‘ – Zur Lehrsteuerung der Studierenden in die Indifferenz - Kamcili-Yildiz, Naciye; Reis, Oliver; Mauritz, Gerrit; Hillebrand, Miriam; Wittke, Annika (Theo-Web. Zeitschrift für Religionspädagogik)

Mindsets religiöser Pluralität als Faktor in der (islamischen) Religionslehrer*innenbildung - Kamcili-Yildiz, Naciye; Mauritz, Gerrit; Reis, Oliver; Wittke, Annika (Theo-Web. Zeitschrift für Religionspädagogik)

Pluralisation of Theologies at European Universities

Säkular und religiös: Herausforderungen für Christentum und Islam

Lesen lernen von Aufgabentexten - Dröse, Jennifer; Prediger, Susanne (Sprachbildender Mathematikunterricht in der Sekundarstufe - ein forschungsbasiertes Praxisbuch)

Physik in der Lehrerinnen- und Lehrerbildung. Auf dem Weg zu empirisch fundierten Curricula - Reinhold, Peter; Riese, Josef (Handbuch Lehrerinnen- und Lehrerbildung)

Die Messung der Fähigkeit zur Unterrichtsplanung im Fach Physik mit Hilfe eines standardisierten Performanztests - Schröder, Jan; Riese, Josef; Vogelsang, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Kulgemeyer, Christoph; Reinhold, Peter; Schecker, Horst (Zeitschrift für Didaktik der Naturwissenschaften)
Zusammenfassung Die Unterrichtsplanung stellt eine zentrale berufliche Anforderung an (Physik‑)Lehrkräfte dar. Bereits im Lehramtsstudium sollen grundlegende Fähigkeiten zur Unterrichtsplanung erworben und im Rahmen von schulpraktischen Phasen erprobt bzw. erweitert werden. Unklar ist jedoch, inwieweit das professionelle Wissen, das Lehramtsstudierende in ihren fachlichen, fachdidaktischen und erziehungswissenschaftlichen Studienteilen erwerben, tatsächlich bei der Planung von Fachunterricht genutzt wird. Ebenso gibt es nur punktuelle Erkenntnisse über die Entwicklung der Fähigkeit zur Unterrichtsplanung im Lehramtsstudium. Um diese Fragen zu klären, sind Messverfahren erforderlich, die die Fähigkeiten zur Unterrichtsplanung valide erfassen können und die gleichzeitig ökonomisch auswertbar sind, um Fallzahlen realisieren zu können, die auch kleine Effekte auflösen. Bisherige Ansätze, die reale Handlungsproben der Unterrichtsplanung (z. B. schriftliche Unterrichtsentwürfe) untersuchen, stehen vor der methodischen Herausforderung, dass die Generierung eines Fähigkeitsmaßes höchst anspruchsvoll ist, da reale Planungen individuell sehr unterschiedlich angelegt sind und vielen Randbedingungen unterliegen, die statistisch kaum kontrollierbar sind. In diesem Beitrag wird daher ein sogenannter Performanztest zur Erfassung der Fähigkeit zur Unterrichtsplanung vorgestellt und diskutiert. Ein Performanztest ist ein Verfahren, in dem in einem realitätsnahen Setting Handlungen unter standardisierten Rahmenbedingungen simuliert werden. Neben der theoriegeleiteten Entwicklung des Instruments und Vorstudien zur Sammlung von Validitätsargumenten werden auch erste Ergebnisse dargestellt, die aus Erhebungen vor und nach einem Praxissemester an vier Universitäten in drei Bundesländern resultieren ( N = 174 Unterrichtsplanungen). Dabei stellt sich das Testverfahren als ausreichend sensitiv heraus, um für N = 68 Testpersonen (ca. 20 % Dropout) erwartungstreu eine signifikante Zunahme des Testscores während des Praxissemesters, welches als Lerngelegenheit angenommen werden kann, zu messen.

Development of Prospective Physics Teachers’ Professional Knowledge and Skills during a One-Semester School Internship - Vogelsang, Christoph; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Reinhold, Peter; Schecker, Horst; Schröder, Jan (Student Learning in German Higher Education)

Professional knowledge affects action-related skills: The development of preservice physics teachers’ explaining skills during a field experience - Kulgemeyer, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan; Vogelsang, Christoph (Journal of Research in Science Teaching)
Keywords: Education

Mindsets guter Lehre in Beziehung zu den Mindsets religiöser Pluralität - Kamcili-Yildiz, Naciye; Reis, Oliver; Mauritz, Gerrit; Hillebrand, Miriam; Wittke, Annika (Theo-Web. Zeitschrift für Religionspädagogik, 19)

The Story of Mary as a Feminine Counterpart to the Story of Joseph - Haghani Fazl, Mohammad (Religious Inquiries, 9)

Adhesion of HVOF-Sprayed WC-Co Coatings on 316L Substrates Processed by SLM - Tillmann, Wolfgang; Hagen, Leif; Schaak, Christoph; Liß, J.; Schaper, Mirko; Hoyer, Kay-Peter; Aydinöz, Mehmet Esat; Garthe, Kai-Uwe (Journal of Thermal Spray Technology)
Abstract Different studies have been demonstrated that the surface integrity of substrate bulk materials to be coated has a significant impact on the adhesion of thermally sprayed coatings. It is known that the surface integrity of parts processed by selective laser melting (SLM) differs from those obtained from bulk materials. Although 316L stainless steel is among the most investigated material for SLM, the adhesion of thermally sprayed coatings on 316L stainless steel substrates processed by SLM has not been studied yet. This study aims at evaluating the effect of various mechanical pre-treatments onto 316L stainless steel substrates processed by SLM and their effect on the adhesion of high velocity oxy-fuel (HVOF)-sprayed WC-Co coatings. To differentiate between topographical effects and residual stress-related phenomena, a stress-relief heat treatment of the SLM substrates served as a reference throughout the investigations. The differently pre-treated SLM substrates were investigated with regard to the surface roughness and residual stresses. For the HVOF-sprayed SLM composites, Vickers interfacial indentation tests were conducted to assess the resulting coating adhesion. The findings demonstrated that the HVOF-sprayed WC-Co coatings predominantly exhibit good adhesion to the SLM 316L substrates. However, it was found that the stress state in the SLM 316L substrate surface is more likely to affect the adhesion of the WC-Co coating, while the substrate surface roughness showed a marginal effect.
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Condensed Matter Physics

Effect of substrate pre‐treatment on the low cycle fatigue performance of tungsten carbide‐cobalt coated additive manufactured 316 L substrates - Tillmann, Wolfgang; Hagen, Leif; Garthe, Kai-Uwe; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Characterization of Phase Transformations During Graded Thermo-Mechanical Processing of Press-Hardening Sheet Steel 22MnB5 - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (Metallurgical and Materials Transactions A)
Abstract Safety-relevant components in automobiles require materials that combine high strength with sufficient residual ductility and high-energy absorption. A graded thermo-mechanical treatment of the press-hardening steel 22MnB5 with graded microstructure can provide a material with such properties. Different austenitization temperatures, cooling and forming conditions within a sheet part lead to the development of microstructures with mixed phase compositions. To determine the resulting phase contents in such graded processed parts, a large number of dilatometric tests are usually required. With a non-contact characterization method, it is possible to detect local phase transformations on an inhomogeneously treated flat steel specimen. For press-hardening steel after heat treatment and thermo-mechanical processing, correlations between austenitization temperature, hot deformation strain, microstructure, and hardness are established.

New Twin-Roll Cast Al-Li Based Alloys for High-Strength Applications - Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko; Belejová, Sára; Králík, Rostislav; Bajtošová, Lucia; Křivská, Barbora; Hájek, Michal; Cieslar, Miroslav (Metals)
Al-Li based alloys are attractive materials for the aerospace industry. The twin-roll casting of such materials could provide properties not achievable by conventional direct-chill casting and downstream processing methods due to significantly higher solidification rates. An Al-Li-Cu-Mg-Zr alloy was twin-roll cast with the same alloy containing a small addition of Sc. The microstructure of as-cast materials and the influence of Sc on the behavior of the alloy at elevated temperatures were studied by means of light and electron microscopy and by resistivity measurements. A fine-grained structure was formed during twin-roll casting, but several surface and internal defects were found on the strips, which should be suppressed by a further adjustment of the casting conditions. The addition of Sc had a positive effect on grain size uniformity and microstructure stabilization at elevated temperatures, as shown by the precipitation of a fine dispersion of coherent Sc- and Zr-containing precipitates.

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)
Zinc oxide (ZnO) hollow spheres with defined morphology and micro-/nanostructure are prepared by a hydrothermal synthesis approach. The materials possess fine-leaved structures at their particle surface (nanowall hollow micro spheres). Morphology control is achieved by citric acid used as an additive in variable relative quantities during the synthesis. The structure formation is studied by various time-dependent ex situ methods, such as scanning electron microscopy, x-ray diffraction, and Raman spectroscopy. The fine-leaved surface structure is characterized by high-resolution transmission electron microscopy techniques (HRTEM, STEM), using a high-angle annular dark field detector, as well as by differential phase contrast analysis. In-depth structural characterization of the nanowalls by drop-by-drop ex situ FE-SEM analysis provides insight into possible structure formation mechanisms. Further investigation addresses the thermal stability of the particle morphology and the enhancement of the surface-to-volume ratio by heat treatment (examined by N2 physisorption).

Strain parameters at hot rolling of aluminum strips reinforced with steel netting - Stolbchenko, Mykhailo; Makeieva, Hanna; Grydin, Olexandr; Frolov, Yaroslav; Schaper, Mirko (Journal of Sandwich Structures & Materials)
This experiment studied the strain parameters of rolling an aluminum matrix when wire netting is inserted between aluminum layers. During the experiment, two types of stainless steel fabric netting oriented parallel and diagonal to the rolling axis were placed between two aluminum strips and rolled. Multiple rolling processes were performed in which the temperature and pressure on the material were varied to produce bonding of matrix layers. During the study, the following main investigations were made: strain on areas of longitudinal and transverse cross sections of the composite was measured; stretching and ovalization of net wiring and changes in the net cell angles were determined; mechanical properties of composites along the rolling direction were tested. The main contradiction resulting from this experiment was as follows: the contact pressure required for the bonding of aluminum layers produces extreme tensile strain on the inserted net wires, reducing the mechanical properties of the reinforcing net and thus reducing properties of the entire composite. Optimal results in the longitudinal tension tests were achieved by using strips with diagonally oriented net-reinforcement.

Characterization of the fatigue behaviour for SAE 1045 steel without and with load-free sequences based on non-destructive, X-ray diffraction and transmission electron microscopic investigations - Wu, Haoran; Bill, T.; Teng, Z.J.; Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko; Starke, Peter (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Tribo-mechanical properties and adhesion behavior of DLC coatings sputtered onto 36NiCrMo16 produced by selective laser melting - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Stangier, Dominic; Hagen, Leif; Schaper, Mirko; Hengsbach, Florian; Hoyer, Kay-Peter (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Degradable silver‐based alloys - Andreiev, Anatolii; Hoyer, Kay-Peter; Grydin, Olexandr; Frolov, Yaroslav; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

The mechanical properties of rolled wire-reinforced aluminum composites at different strain values - Stolbchenko, Mykhailo; Frolov, Yaroslav; Makeieva, Hanna; Grydin, Olexandr; Tershakovec, Michael A.; Schaper, Mirko (Mechanics of Advanced Materials and Structures)

Effect of substrate pre‐treatment on the low cycle fatigue performance of tungsten carbide‐cobalt coated additive manufactured 316 L substrates - Tillmann, Wolfgang; Hagen, Leif; Garthe, Kai-Uwe; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)

Adhesion of HVOF-Sprayed WC-Co Coatings on 316L Substrates Processed by SLM - Tillmann, Wolfgang; Hagen, Leif; Schaak, Christopher; Liß, Jan; Schaper, Mirko; Hoyer, Kay-Peter; Aydinöz, Mehmet Esat; Garthe, Kai-Uwe (Journal of Thermal Spray Technology)
Abstract Different studies have been demonstrated that the surface integrity of substrate bulk materials to be coated has a significant impact on the adhesion of thermally sprayed coatings. It is known that the surface integrity of parts processed by selective laser melting (SLM) differs from those obtained from bulk materials. Although 316L stainless steel is among the most investigated material for SLM, the adhesion of thermally sprayed coatings on 316L stainless steel substrates processed by SLM has not been studied yet. This study aims at evaluating the effect of various mechanical pre-treatments onto 316L stainless steel substrates processed by SLM and their effect on the adhesion of high velocity oxy-fuel (HVOF)-sprayed WC-Co coatings. To differentiate between topographical effects and residual stress-related phenomena, a stress-relief heat treatment of the SLM substrates served as a reference throughout the investigations. The differently pre-treated SLM substrates were investigated with regard to the surface roughness and residual stresses. For the HVOF-sprayed SLM composites, Vickers interfacial indentation tests were conducted to assess the resulting coating adhesion. The findings demonstrated that the HVOF-sprayed WC-Co coatings predominantly exhibit good adhesion to the SLM 316L substrates. However, it was found that the stress state in the SLM 316L substrate surface is more likely to affect the adhesion of the WC-Co coating, while the substrate surface roughness showed a marginal effect.

Adhesion of HVOF-Sprayed WC-Co Coatings on 316L Substrates Processed by SLM - Tillmann, W.; Hagen, L.; Schaak, C.; Liß, J.; Schaper, Mirko; Hoyer, Kay-Peter; Aydinöz, M. E.; Garthe, Kai-Uwe (Journal of Thermal Spray Technology)
Abstract Different studies have been demonstrated that the surface integrity of substrate bulk materials to be coated has a significant impact on the adhesion of thermally sprayed coatings. It is known that the surface integrity of parts processed by selective laser melting (SLM) differs from those obtained from bulk materials. Although 316L stainless steel is among the most investigated material for SLM, the adhesion of thermally sprayed coatings on 316L stainless steel substrates processed by SLM has not been studied yet. This study aims at evaluating the effect of various mechanical pre-treatments onto 316L stainless steel substrates processed by SLM and their effect on the adhesion of high velocity oxy-fuel (HVOF)-sprayed WC-Co coatings. To differentiate between topographical effects and residual stress-related phenomena, a stress-relief heat treatment of the SLM substrates served as a reference throughout the investigations. The differently pre-treated SLM substrates were investigated with regard to the surface roughness and residual stresses. For the HVOF-sprayed SLM composites, Vickers interfacial indentation tests were conducted to assess the resulting coating adhesion. The findings demonstrated that the HVOF-sprayed WC-Co coatings predominantly exhibit good adhesion to the SLM 316L substrates. However, it was found that the stress state in the SLM 316L substrate surface is more likely to affect the adhesion of the WC-Co coating, while the substrate surface roughness showed a marginal effect.